Княжна Джаваха: повесть / Лидия Чарская - Чарская Лидия Алексеевна (Серия "Внеклассное чтение", 2009)
Экземпляры: ф. 1 (20091210) / Инвентарный номер: 95648 / Цена: 148.50 / Авт.знак: Ч-22 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)1